2019
DOI: 10.1186/s12887-019-1834-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuropsychiatric comorbidities and their clinical characteristics in Chinese children with asthma using the MINI kid tool

Abstract: BackgroundThe mental health and quality of life in children with asthma have attracted widespread attention. This study focused on the evaluation of mental health conditions and their clinical characteristics in Chinese children with asthma.MethodsA total of 261 children with asthma aged 6 to 16 years old and 261 age- and gender-matched children from the general population were recruited to participate in this study from Guizhou Provincial People’s Hospital. The parents of all subjects were interviewed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The prevalence of common childhood neurodevelopmental disorders such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) has increased during the last few decades 74,75 . The corresponding increasing comorbid conditions of asthma with neurodevelopmental disorders have a more substantial impact on children, carers and society than asthma alone 76 . Despite this fact, clinical guidelines for asthma or neurodevelopmental disorders often overlook the existence of possible comorbidities 77 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of common childhood neurodevelopmental disorders such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) has increased during the last few decades 74,75 . The corresponding increasing comorbid conditions of asthma with neurodevelopmental disorders have a more substantial impact on children, carers and society than asthma alone 76 . Despite this fact, clinical guidelines for asthma or neurodevelopmental disorders often overlook the existence of possible comorbidities 77 .…”
Section: Resultsmentioning
confidence: 99%
“…74,75 The corresponding increasing comorbid conditions of asthma with neurodevelopmental disorders have a more substantial impact on children, carers and society than asthma alone. 76 Despite this fact, clinical guidelines for asthma or neurodevelopmental disorders often overlook the existence of possible comorbidities. 77 One particular challenge for children with concurrent asthma and ADHD and their parents is adequate disease management, such as appropriate use of inhalers, as well as stress and anxiety management to avoid asthma exacerbations.…”
Section: Asthma and Neurodevelopmental Disordersmentioning
confidence: 99%
“…Another study reported that patients with TS who also suffer tics that resemble asthma symptoms were often diagnosed with asthma and received asthma treatments. 26 On the other hand, asthma is reported to be associated with several psychiatric disorders including TD. 27 Many children with TS are incorrectly diagnosed and treated for asthma or rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that children with TD often present eczema, allergic rhinitis, allergic conjunctivitis, asthma, or other allergic diseases. [13][14][15] Therefore, the relationship between TD and allergic diseases has gained attention among scientists and requires further study. Analysis of the lymphocyte subpopulation in TD suggests a possible systemic activation of several T cell and B cell subtypes.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation